Quantum confinement and photoresponsivity of β-In2Se3 nanosheets grown by physical vapour transport - Balakrishnan, Nilanthy; Staddon, Christopher R.; Smith, Emily F.; Stec, Jakub; Gay, Dean; Mudd, Garry W.; Makarovsky, Oleg; Kudrynskyi, Zakhar R.; Kovalyuk, Zakhar D.; Eaves, Laurence; Patanè, Amalia; Beton, Peter H. (IOP Publishing, 2016)
We demonstrate that β-In2Se3 layers with thickness ranging from 2.8 – 100 nm can be grown on SiO2/Si, mica and graphite using a physical vapour transport method. The β-In2Se3 layers are chemically stable at room temperature and exhibit a blue-shift of the photoluminescence emission when the layer thickness is reduced, due to strong quantum confinement of carriers by the physical boundaries of the material. The layers are characterized using Raman spectroscopy and X-ray diffraction from which we confirm lattice constants c = 28.31±0.05 Å and a = 3.99±0.02 Å. In addition, these layers show high photoresponsivity of up to ~ 2×103 A/W at λ = 633 nm, with rise and decay times of τr = 0.6 ms and τd = 2.5 ms, respectively, confirming the potential of the as-grown layers for high sensitivity, fast photodetectors.